Psychological therapies for the management of co-morbid depression following a spinal cord injury: A systematic review. (December 2014) - Perkes, Sarah J; Bowman, Julia; Penkala, Stefania
The evidence about psychological therapies used to manage co-morbid depression after a spinal cord injury is presented here. A comprehensive search of five electronic databases identified nine studies (participants, n = 591) meeting inclusion criteria. Pooled statistical analyses were conducted in combination with narrative synthesis. Overall, multimodal cognitive behavioural therapy was found to be moderately effective (standardised mean difference = −0.52; 95% confidence interval = −0.85, −0.19). Activity scheduling, psychoeducation, problem solving and cognitive therapy may be particularly beneficial therapies within cognitive behavioural therapy. Further high-quality randomised controlled trials are needed to better substantiate these findings.